Effect of the charge state of traps on the transport current in the SiC/Si heterostructure - Lysenko, V.S.; Tyagulski, I.P.; Gomeniuk, Y.V.; Osiyuk, I.N. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2000)
Forward and reverse currents in the heterostructure “amorphous SiC/p-Si” were studied in the temperature range 30 – 80 K. It has been found that in different ranges of the applied voltage the transport current is described by different mechanisms. Charging the electron traps situated in the SiC layer increases the forward current due to reduction of the potential barrier for holes. In the range of forward biases 0.5 – 0.8 V the current is controlled by variable-range hopping of holes in the amorphous SiC according to the Mott's mechanism. At higher voltages the dominant mechanism controlling the current becomes the hole tunneling across the triangular barrier in the amorphous-crystalline semiconductor interface.